2011
DOI: 10.1128/cvi.00017-11
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Magnitude of Antibody Responses against the Conserved 47-Kilodalton Antigen and the Variable 56-Kilodalton Antigen in Scrub Typhus Patients

Abstract: Western blot analysis of Orientia tsutsugamushi whole-cell lysates with scrub typhus patient sera has identified at least five protein antigens of O. tsutsugamushi with molecular sizes of 22 kDa, 47 kDa, 56 kDa, 58 kDa, and 110 kDa. In this study, sera from serial bleedings of 108 patients were used to study the kinetics and the magnitude of specific antibody responses against the 47-kDa and 56-kDa antigens. Recombinant protein of the conserved 47-kDa antigen (r47b) or a mixture of truncated 56-kDa antigen (r5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Previously, it was suggested that the 47-kDa protein, an HtrA homolog of O. tsutsugamushi, might be a useful antigen if combined with TSA56 for serological diagnosis (8,15). However, specific antibody titers against the 47-kDa antigen in human patients are relatively low during the acute phase of infection (8), which might be due to antibody cross-reaction with human serine protease or HtrAs of other bacteria (7). We also consistently observed relatively low levels of specific antibody responses against the 47-kDa antigen in our human patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was suggested that the 47-kDa protein, an HtrA homolog of O. tsutsugamushi, might be a useful antigen if combined with TSA56 for serological diagnosis (8,15). However, specific antibody titers against the 47-kDa antigen in human patients are relatively low during the acute phase of infection (8), which might be due to antibody cross-reaction with human serine protease or HtrAs of other bacteria (7). We also consistently observed relatively low levels of specific antibody responses against the 47-kDa antigen in our human patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of this assay, which were calculated from confirmed and non-scrub typhus patients, were 86.5% (95% CI: 74.2 to 94.4) and 100% (95% CI: 97.3 to 100), respectively. In addition, using real-time PCR and IFA results, we identified five patients with secondary infection characterized by a high IgG titer with a relatively low IgM titer (12). Among these patients, four exhibited a high (Ն1:3,200) IgG titer, with or without an apparent 4-fold increase; a relatively low IgM titer (Յ1: 400); and positive PCR results.…”
Section: Resultsmentioning
confidence: 99%
“…ELISA was performed as previously described [61]. The cutoff was determined by using the mean of the sham group plus 1.745 times the standard deviation for the 95% confidence interval [62].…”
Section: Recombinant Protein Antigen Based Elisa For Antibody Detectionmentioning
confidence: 99%